Bundo Kanduang: (hanya) Pemimpin di Rumah (Gadang) - Arifin Zainal (Antropologi Indonesia, 2013)
Minangkabau ethnic group known is very strictly implement custom of matrilineal. One of these values is male position (sumando) that marginal, because according to matrilineal custom, a man is urang asing (outsiders) in the group of women (wife families). This is expressed through the proverb bak abu diateh tunggua (like ashes on the stump). This position of course is not profitable, so that they have to negotiate with the women to strengthen “the identity of maleness" of them. It shows the politics movement of Minangkaba’s men in an effort to show and strengthen their identity. This political identity of Minangkabau’s man will be understood identity politics Minangkabau men will be understood in the case of the existence of traditional institutions. The research assumption, in Minangkabau society that embraces and strengthens matrilineal custom (women custom) was found that traditional institutions more dominated by men. While traditional institutions for women does not stand out, impress hidden, and there is no variation than bundo kanduang (the main women). This article to described how men of Minangkabau through traditional institutions reinforce the position, while the bundo Kanduang’s position only limited powers in rumah gadang alone. Moreover, bundo Kanduang understood even without any power, because bundo kanduang just as the wife of penghulu (clan leaders).Keywords: duality , political identity, Minangkabau custom, traditional institutions